A Deconstructive stylistic reading of Keats' Ode on a Grecian Urn - Prashant Mishra (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
The present paper applies Deconstructive Stylistics on John Keats’ Ode on a Grecian Urn. Stylistics that evolved from the Structuralist movement in literature makes use of the formal criterion in linguistics in the reading of literary texts. It treats a text as an autonomous entity and aims at objective description of the lexical, syntactical and phonological features in order to explore the meaning of a text. Stylistics is often seen as an attempt to put criticism on a scientific basis. Deconstruction, contrary to Stylistics, regards a text as an open-ended entity without a core or a centre to assign it absolute and final signification. Deconstruction initiates its premise from de Saussure’s concepts of ‘difference’ and ‘binary opposition’ and extends them to ‘differance’ to recognize the indefinite, ambiguous and intertextual nature of a text that leads to postponement of signification. A deconstructionist believes that a writer is never able to express what he intends to express through his writings and therefore always leaves a trace and a critic; therefore, he has to engage himself in the endless pursuit of exploring the intended meaning of the writer. Deconstructive criticism hence becomes an attempt to read a text in order to approximate the intended meaning of the writer. Keats’ odes are the finest examples of entertaining mysteries, doubts and uncertainties surrounding the questions pertaining to human existence through imagination rather than a rational outlook. The annihilation of self, anti-egoistic stand, skeptical attitude towards things and the conflicting moods towards different aspects of themes provide a fine deconstructive reading of Keats’ odes. The present paper endeavours to explore the formal stylistic means and grammatical devices employed by Keats in Ode on a Grecian Urn to escape any finality, absoluteness, resolution and unification of the opposites.